Erosional researches in a sandstone gully in the Medves region - Hegedűs, Krisztián; Karancsi, Zoltán; Horváth, Gergely (JOURNAL OF LANDSCAPE ECOLOGY, 2007)
The Karancs – Medves Landscape Protection Area is founded in the Northern Middle Mountain. The development of its surface, special natural beauties have already been studied by several researchers. The Medves territory is part of the Northern Middle Mountain where we can find several landforms formed by linear erosion. Some of these gullies can be tourist attractions as well. We chose a sandstone gully out of them as our study area. This gully is formed by Csobán-Berek stream, which flows from the South-Western edge of the Medves Plateau. The local name of this small gully is Ravasz-Lyuk. The studied area is partially covered by sediment and its spreading is about 1 km2. Field measurements, which are the basis of the research, have been doing for six months every second week. Using assigned measuring points in the main line we could point out the changes of the water-course’s figure, rain water ability for sediment transportation and other geomorphological processes (crumbling, sliding etc.), which are typical for the lines of the studied gullies. The measuring points were assigned by steel bars, with which we could document the changes relatively precisely. The observation of the sediment transportation was completed by painted rocks (sandstone, trap). Finding out the rate of accumulation and the brought down sediment played important role in our research. We used different methods to calculate the rate as punctually as it is possible. Territories, which are not part of the assigned areas are studied by photographs taken different times. This method sometimes more efficiently shows the differences between two landforms than complicated methods. We fulfilled the correction of the gully lines with the help of GPS during our work. We used a topographical map (1:10 000), made at the end of the 1980’s, as the basis of data correction. Our results are presented by tables, diagrams, thematic maps and ranges of photos.The study was supported by OTKA (T 048734).
Keywords: erosion; sandstone gully; Medves Region